Processamento lexical em bilíngues espanhol-português: um estudo sobre a influência da L2 na L1 a partir do efeito de congruência de gênero - Souza, Rodrigo Andrade de (2023)
In the field of studies on bilingualism, several studies have found evidence of bilingual interlingual influences at the lexical level. Studies on how grammatical gender information is processed in the minds of bilinguals have reached different conclusions. In this context, we seek, in general, to verify how grammatical features are shared between the languages of bilingual speakers. In the direction of analyzing interlingual influences (L2-L1), we carried out our experiment with Spanish-Portuguese bilinguals living in Brazil in order to seek answers to our initial concerns. The experiment was divided into two parts: the first dedicated to the Selfpaced Reading task and the second dedicated to the Brazilian Portuguese Lexical Verification Test (TVLPB) (Sá, Alves Santos, Souza, Amaral, Almeida, 2021). For the self-paced reading task, experimental sentences were constructed in the participant’s L1, Spanish, controlling two two-level predictor variables: the gender congruence/congruence of the nouns and the agreement/non-agreement of the adjectives that accompanied them. The participant’s L2 proficiency, Portuguese, was our third predictor variable. Our results demonstrated that adjective response times decrease as Portuguese proficiency increases. However, this decrease is significantly more pronounced in the condition of non-concordance between noun and adjective. We deal with the hypothesis of the existence of interlinguistic influences in the minds of bilingual individuals at the time of processing, which converges with the studies carried out by Bordag and Pechmann (2007), Lemhöfer, Spalek and Schriefers (2008), Paolieri et al. (2010) and Kaushanskaya and Smith (2015). In case of bidirectional influence, from L1 to L2, we agree with Bordag and Pechmann (2007); Lemhöfer, Spalek and Schriefers (2008) and Paolieri et. al. (2010); from L2 to L1, we are in accordance with Bordag and Pechmann (2007) and Kaushanskaya and Smith (2015). Finally, we assume that the more the bilingual's L2 proficiency increases, the more frequent her lexical items become in her mental lexicon. This is a consequence of high exposure to L2 (Dijkstra et al., 2019).